Rastreio de mutação do gene BRCA1 em pa cientes com câncer de mama atendidos em uma unidade de saúde do Estado do Amazonas / Amanda de Araújo Rocha. - Rocha, Amanda de Araújo (2019)
Breast cancer can be defined as a heterogeneous disease of multifactorial character, there are a number of risk factors for breast development, including hereditary factors, hormones, age, physical inactivity, alcohol, radiation and obesity. Mutations in the BRCA1 gene are responsible for 50% of hereditary breast cancer cases. The aim of this study was to characterize a group of patients treated at the Amazonas State Oncology Control Center Foundation (FCECON) regarding hereditary breast cancer risk factors. This study was carried out at the Proteomics and Genomics Laboratory of the EU, using direct sequencing of 8 exons of the BRCA1 gene. Patients with myocardial revascularization syndrome, with family history of predisposition and risk of hormonal life. Changes in gene data have been verified in existing databases for this gene (ClinVar, BRCA Exchange and Varsome). The 4 forms of mutation that are missense mutation c.4304T> C exon 13 (16 patients), missense mutation c.4837A> G exon 16 (25 patients), frameshifth mutation c.5266dupC exon 20 (1 patient) and mutation were studied. intronic c.5277 + 48_5277 + 59dup (1 patient). Of the 53 patients studied, 26 had mutations, where only one patient had a disease-based mutation, a mutation of c.4837 A> G was frequent in 25 patients ruling out a possibility of being deleterious. As mutations have reported that studies have not yet had data on industry developments in the literature, which is particularly necessary so that they cannot have a BRCA1 gene in the Brazilian and worldwide population. Therefore, what is most important for the development of new future series is that the Brazilian knowledge pattern is mutational for high-capacity breast cancer genes such as BRCA1. Key words: Breast cancer, hereditary cancer syndrome, BRCA1.